Factors contributing to home deliveries by women attending post-natal care at a selected clinic in Rundu District, Kavango East Region, Namibia - Daniel O. Ashipala; Tatenda Mutsindikwa (AOSIS, 2022)
In 2016, almost 31 million births in low- and middle-income countries occurred without a qualified birth attendant. 90% were in South Asia and sub-Saharan Africa. In sub-Saharan Africa, where Namibia is located, 50% of births are unattended. This study aimed at identifying factors contributing to home births in Rundu District, Kavango East Region. This study was quantitative cross-sectional. Postnatal moms who gave birth at home completed a self-administered questionnaire with closedended questions. 27.2% of respondents were 33 to 38. Most responders (83.3%) were unmarried and 38.6% were "other" religious. Participants were mostly unemployed (79.8%). 49.1% of respondents were uneducated. 8.8% of employed people were in the public sector, 6.1% in private, and 1.8% self-employed. Most (93.9%) visited antenatal clinics once (25.4%), twice (20.2%), or three times (40%) before delivery. 81% picked where to deliver on their own, and 71% had previously delivered at home. No one explained this behavior. The majority of women in this study had given delivery at home. Education, religion, and delivery location were correlated. These findings inform the community and government about the present trend of home births, which may harm mother and newborn outcomes.